Planting for Energy in Orissa - Das, M. C. (Indian Forester, 1981)
The fuelwood demand in Orissa is likely to increase from 6 million m3 (1970-71) to about 9 millioo m3 by the year 2000 A.D. Due to excessive burning of cattle during the fertiliser consumption in the State is quite low and thus the per hectare productivity under agriculture is quite unfavourable as compared to other States. Therefore extensive stretches of wastelands, roadside and rail line lands can be put under energy plantations. For promoting energy plantations different approaches are indicated for production forestry, extension forestry and community forestry. Intensive fuelwod cultivation or fuel gardening in villagers back-yard is recommended. Extension measures and demonstration plots will provide encouragement to villagers to grow more trees on farm lands and private holdings. Besides statutary protection and fencing of planted areas, peoples partictipation and cooperation are needed to prevent the energy plantation from grazing and pilferage. Merely growing more wood is not sufficient to end deprivation but equitable distribution system has to be built up in the programme of community forestry and energy plantations.